CHINESE INVOLVEMENT IN VANUATU AND SOLOMON ISLAND FOREIGN POLICY AGAINST THE PAPUA ISSUE - Marinus Mesak; Yanyan Mochamad Yani; Windy Dermawan (Sociae Polites, 2020)
The influence of China in the Pacific region increases due to the Belt and Road Initiative (BRI) program that focuses its assistance and soft loans on the development of basic infrastructure and other supporting infrastructure. Increased economic influence has an impact on changes in regional geopolitical maps. China appears to be increasingly dominant in influencing the foreign policy of the region’s countries, including China’s involvement in controlling Vanuatu and Solomon Island’s foreign policy. At present, the issue of Papua is on the main agenda of Vanuatu and Solomon Island’s foreign policy. Significant funds are needed to finance the process of advocating for the issue of Papua in the Pacific region and the international community. One source of funding comes from Chinese aid. This article will review China’s position as a source of the financing for the Papuan separatist movement based in Vanuatu and Solomon Islands, by using a power approach and economic diplomacy. Keywords: China, Belt, and Road Initiative, economic, diplomacy, Power, Vanuatu, Solomon Island, and Internationalization of Papuan Issues.